ChemInform Abstract: Our Odyssey with Functionalized Chiral Phosphines: From Optical Resolution to Asymmetric Synthesis to Catalysis. Issue 16 (March 2016) - Chew, Renta Jonathan; Leung, Pak‐Hing
Abstract: Review: [60 refs.